Avaliação de fatores que interferem na metodologia de análise e na longevidade de restaurações adesiva - Vilela, Ana Laura Rezende (2021)
Several factors can influence the longevity of restoration: restorative protocol, material, as well as patient care with the restoration. The general objective of this study was to evaluate the factors that can interfere in the analysis methodology and in the longevity of adhesive restorations. Thus, this study was divided into 4 chapters according to each specific objective: Chapter 1) Evaluate the influence of the time interval, between corrosive and abrasive challenges (immediate, 15 minutes and 30 minutes), on surface roughness and hardness of a nanoparticulate composite resin; Chapter 2) Analyze the influence of different parameters on the microshear methodology, such as the thickness of the orthodontic wire (0.2 mm and 0.7 mm) and the distance between the specimens (1.5 and 3 mm), on the bond strength and stress distribution of a lithium disilicate ceramic; Chapter 3) Evaluate the effectiveness of different silanes (prehydrolyzed and immediate hydrolysis), in the form of storage (at room temperature or at 5ºC) and in the bond strength of composite resin repair and Chapter 4) Influence of hydrolytic stability on the bond strength of silanes and a universal adhesive in composite resin repairs. The experimental methods used were: roughness (chapters 1); microhardness (chapter 1); scanning electron microscopy (chapters 1, 2, and 3); microshear (chapters 2, 3 and 4); finite element analysis (chapter 2); contact angle (chapter 3). The results showed that: 1) Immersion in an acid beverage, immediately followed by brushing with bleaching paste, increased the surface roughness of the composite resin; the 30- minute interval between drinking acidic beverage and brushing was shown to be important to reduce the deleterious effects of composite resin restorations; and microhardness was not influenced by the interval between drinking acidic beverage and brushing; 2) The diameter of the orthodontic wire influenced the microshear bond strength, and the wire with a diameter of 0.2mm had better adhesion values and the distances between the specimens (1.5 or 3mm) did not influence the strength bonding and stress concentration of the materials used; 3) The silane and the storage form, after opening, influenced the bond strength in composite resin repairs. The pre-hydrolyzed silane initially presented higher bond strength and the immediate hydrolysis silane maintained adhesion values after - 14 - one year of storage at room temperature, when compared to storage at 5ºC. 4) The hydrolytic stability of the silane was worse for the pre-hydrolyzed silane. After the aging process, the universal adhesive showed higher adhesion values when compared to pre-hydrolyzed or immediate hydrolysis silanes. It can be concluded that brushing and the ingestion of acidic beverages can influence the roughness of the nanoparticulate composite resin and that the pre-hydrolyzed silane is an unstable product, regardless of aged with the sealed bottle or after it has already been used and that the method of production of samples for microshear testing may interfere with the final results